2011
DOI: 10.2172/1011223
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine composite blade manufacturing : the need for understanding defect origins, prevalence, implications and reliability.

Abstract: Renewable energy is an important element in the US strategy for mitigating our dependence on non-domestic oil. Wind energy has emerged as a viable and commercially successful renewable energy source. This is the impetus for the 20% wind energy by 2030 initiative in the US. Furthermore, wind energy is important on to enable a global economy. This is the impetus for such rapid, recent growth. Wind turbine blades are a major structural element of a wind turbine blade. Wind turbine blades have near aerospace quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…A 2008 study by Sandia National Laboratory found that 7% of wind turbine blades had to be replaced before reaching their expected lifetime. Due to each turbine having three blades, the chance of downtime caused by a blade failure is tripled (Cairns, Riddle, & Nelson, 2011). According to Sandia, blades have been responsible for 11% of turbine downtime recently.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2008 study by Sandia National Laboratory found that 7% of wind turbine blades had to be replaced before reaching their expected lifetime. Due to each turbine having three blades, the chance of downtime caused by a blade failure is tripled (Cairns, Riddle, & Nelson, 2011). According to Sandia, blades have been responsible for 11% of turbine downtime recently.…”
Section: Motivationmentioning
confidence: 99%
“…The MSUCG is a third party investigator tasked with investigating the Effects of Defects. This has been broken into two subtasks (Cairns, Riddle, & Nelson, 2011):…”
Section: Standards and Partnershipsmentioning
confidence: 99%
“…The damage should be understood as changes to the constitutive material and/or the geometric properties, including alterations to the boundary conditions and structural connectivity, which can adversely affect structural and power performance . Thus, several issues have been studied, eg, manufacturing process, fracture, fatigue, and adhesive joints . Although diverse turbine designs exist, currently the most common design is built in an upwind horizontal axis with three blades.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively large numbers of repairs and early replacements are required ("Blade failure and load monitoring," 2008; Campbell, 2015). While many issues are related to the used manufacturing processes (Cairns et al, 2011;Nielow, 2014), this also indicates a need for detailed structural analysis to improve the understanding of the structure's behavior. This is possible by means of detailed finite element (FE) analysis.…”
Section: Introductionmentioning
confidence: 99%